D’hulst, L., & Gambier Y. (Eds.). (2018). A history of modern translation knowledge: Sources, concents, effects. Amsterdam: John Benjamins. 475 pp. - van Egdom, Gys-Walt (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Book review